Profile of the using antihypertension pre-eclampsia patients at hospital - Mayasari, Shinta; Dwi Qurniah Febriyanti (Jurnal EduHealth, 2024)
Pre-eclampsia was a class of hypertension in pregnancy. Based on WHO in 2015 the prevalence of preeclampsia in developed countries was around 1.3-6% while in developing countries it was around 1.8-18%. Antihypertensive therapy in pre-eclampsia patients was calcium channel blockers. Nifedipine was a dihydropyridine calcium channel blocking agent used as a first-line antihypertensive treatment for pre-eclampsia. The used of hypertension drugs in pregnancy can be said to be successful and effective when blood pressure reaches the target of <140/90 mmHg. The purposed of this study was to analyze the profile of the effectiveness of using nifedipine in pre-eclampsia patients at Hospital. This research was a quantitative research with a retrospective descriptive design. The total sample was 91 patients. The data source used medical record data from pre-eclampsia patients at Hospital in the 2022 period. The sampling used was simple random sampling technique and data was displayed in the form of frequency and percentage. The results of this studied indicate that the used of the drug nifedipine 10 mg (13%) nifedipine 3x10 mg (87%), the average blood pressure before 161.37/101.26 mmHg, the average blood pressure after 132.97/85.60 mmHg and the effectiveness of using nifedipine was 100% effective. Thus it could be concluded that the profile of the effectiveness of using nifedipine was said to be effective because it could reduce blood pressure. Nifedipine was recommended in pre-eclampsia patients to lower blood pressure